Structures of Pseudo - BG Algebra and Sime pseudo – BG - Algebra - Shwan Adnan Bajalan; Rasti Raheem Mohammed Amin; Aram K. Bajalan (Tikrit Journal of Pure Science)
In this paper, we introduced the notion new types of algebras pseudo BG- algebra, pseudo sub BG –algebra, Pseudo Ideal and pseudo strong Ideal of Pseudo-BG-Algebras. We state some Proposition and examples which determine the relationships between these notions and some types of ideal and we introduced the notion semi pseudo BG- algebra, pseudo sub BG –algebra, Pseudo Ideal and pseudo strong Ideal of semi   pseudo-BG-Algebras. We investigated a new notion, of algebra called semi pseudo BG- algebra. We state some Proposition and examples which determine the relationships between these notions and some types of ideals defined minimal and homomorphism and kernel.